2016
DOI: 10.1371/journal.pone.0153652
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genetic Diversity of Enteric Viruses in Children with Diarrhea in Ouagadougou, Burkina Faso

Abstract: Enteric viruses are a major cause of diarrhea in children, especially those under five years old. Identifying the viral agents is critical to the development of effective preventive measures. This study aimed to determine the prevalence and genetic diversity of common enteric viruses in children under five years old in Burkina Faso. Stool samples from children with (n = 263) and without (n = 50) diarrhea disorders were collected in Ouagadougou, Burkina Faso from November 2011 to September 2012. Rotavirus, noro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
97
14
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(141 citation statements)
references
References 79 publications
29
97
14
1
Order By: Relevance
“…This disparity amongst studies may be due to the number of viruses analyzed, viral detection methods, season of sampling, and sample size. The most common coinfections were between RVA and HAstV which is in contrast with reports of Biscaro et al, Ferreira et al, and Ouédraogo et al who had RVA and HAdV as the most prevalent. Pang and Vesikari previously reported the rate of HAstV and RVA coinfections among gastroenteritis in children to be extremely low (10 of 1528 or 0.006%).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This disparity amongst studies may be due to the number of viruses analyzed, viral detection methods, season of sampling, and sample size. The most common coinfections were between RVA and HAstV which is in contrast with reports of Biscaro et al, Ferreira et al, and Ouédraogo et al who had RVA and HAdV as the most prevalent. Pang and Vesikari previously reported the rate of HAstV and RVA coinfections among gastroenteritis in children to be extremely low (10 of 1528 or 0.006%).…”
Section: Discussioncontrasting
confidence: 99%
“…A relatively low frequency of coinfection (9.7%) was observed in this study, which is lower than previously reported in Burkina Faso (35.7%) and Brazil (14%), but higher compared with studies from China (5.2%), Northern Italy (2.3%), and Nigeria (7.1%) . This disparity amongst studies may be due to the number of viruses analyzed, viral detection methods, season of sampling, and sample size.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…AdV all types were detected using a commercial real-time PCR assay designed to detect all types of human AdV (Adenovirus R-gene™, Argène, Verniolle, France) and AiV were detected by end-point RT-PCR using the Qiagen One-Step RT-PCR kit (Qiagen, Hilden, Germany) and the primer set Ai6261/Ai6779 [20]. …”
Section: Methodsmentioning
confidence: 99%
“…NoV detection was performed by real-time RT-PCR as previously described [1]. A total of 222 stool samples, corresponding to 87 outbreaks (76%), were positive for norovirus.…”
Section: Laboratory Investigationmentioning
confidence: 99%